RPA-CRISPR-Cas-Mediated Dual Lateral Flow Assay for the Point-of-Care Testing of HPV16 and HPV18 - Zhang, Kaini; Li, Qingmei; Wang, Kun; Zhang, Qiaoli; Ma, Chengkun; Yang, Guiwen; Xie, Yanxia; Mauk, Michael G.; Fu, Shanji; Chen, Lei (Bioconjugate chemistry, 2024)
The incidence of cervical cancer caused by human papillomavirus (HPV) infection has increased in recent years. More than half of all cervical cancer cases are due to HPV16 and HPV18 infection, so HPV16 and HPV18 testing is essential to prevent cervical cancer. HPV testing is mainly carried out in hospitals, but it is subject to time and specialized medical facilities. On the other hand, home self-testing using simple diagnostics would present an attractive alternative due to privacy and flexibility with regard to time and place, provided sufficient sensitivity and specificity can be achieved. In this work, a dual lateral flow assay based on RPA-CRISPR-Cas12a/13a (named RC-LFA) for HPV detection was described. Taking advantage of the cleavage specificity of Cas12a and Cas13a, a CRISPR-Cas12a/Cas13a system was designed to detect HPV16 and HPV18. The lateral flow strip with two test lines was designed to suit the CRISPR-Cas12a/Cas13 system. RC-LFA achieves rapid and simultaneous detection of HPV16 and HPV18 with high specificity and sensitivity (10 copies/μL) in about 40 min from the extraction of nucleic acid to an instrument-free readout. RC-LFA is user-friendly and instrument-free, making it a promising method for HPV self-tests at home.